Discourse and Mediation: A Historical Overview of Theoretical Narratives and Research Agendas - Chouliaraki, Lilie (The Greek Review of Social Research, 2025)
This article examines key conceptualizations of discourse that have shaped scholarly analyses of mediation, communicative networks, and practices of digital modernity across the social sciences and humanities throughout the 20th century. It traces four influential frameworks through which discourse has been appropriated: (1) discourse as communicative power, (2) discourse as popular empowerment, (3) discourse as the textualization of power, and (4) discourse as symbolic power. These frameworks reveal distinct analytical orientations to the political and popular dimensions of mediation, and reflect varying understandings of the power of discourse as shaped through language and visuality in the construction of social realities. The article concludes by briefly addressing how these conceptualizations of discourse and power are being reconfigured in the context of machine learning, algorithmic mediation, and big data in the digitized landscape of the 21st century.